Variation of Epithelial and Nuclei Morphohistology in Oral Submucous Fibrosis Patients: Epithelial and Nuclei Morphohistology in Oral Submucous Fibrosis Patients - Ahmed, Rida Rubab; Qureshi, Maryam Faiz; Bashir, Sibgha; Abideen, Zen Ul; Zafar, Adeel; Hafeez, Rizwan; Haque, Mazhar Ul (Pakistan Journal of Health Sciences, 2025)
In the background of oral submucous fibrosis, oral cancer is the most commonly present malignant transformation in South Asian regions. Alteration of tissue architecture contributes significantly to determine the exact pathological state of the disease. Objective: To evaluate histological changes in structure of oral submucous fibrosis patients in context of textural properties of epithelium and morphology of nuclei. Methods: A total of 50 subjects were inducted in this cross-sectional study performed at dentistry department of Jinnah Postgraduate Medical Center (JPMC) in Karachi. Punch biopsy samples were taken from buccal mucosa followed by preparation of tissue blocks and slide preparation to analyze histology of premalignancy and record abnormal features present in normal oral tissue. Results were analyzed through SPSS version 23.0 and p value of ≤0.05 was considered as statistically significant. Results: 37 (74%) subjects had prominent Oral Submucous Fibrosis histologically out of which abnormal epithelial parameters such as stratified squamous, hyperplastic, keratotic, and neoplastic were noted in 5 (10%), 31 (62%), 10 (2%), 0 (0%) subject respectively. p value 0.041 was calculated using Chi square analysis for qualitative data which depicted relevance of hyperplastic epithelium in Oral Submucous Fibrosis. 29 (87.9%) subjects showed pleomorphism in nucleus and 8 (47.1%) showed normal/round nucleus in Oral Submucous Fibrosis subjects with a p value of 0.003. Conclusions: Histological analysis which is not routinely performed in oral submucous fibrosis patients could visualize accurate extent of disease through structural variability of epithelium and nucleus.